2016
DOI: 10.1080/0284186x.2016.1253866
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomized study of the IGF-1R pathway modulator AXL1717 compared to docetaxel in patients with previously treated, locally advanced or metastatic non-small cell lung cancer

Abstract: Harmenberg (2017) Phase II randomized study of the IGF-1R pathway modulator AXL1717 compared to docetaxel in patients with previously treated, locally advanced or metastatic non-small cell lung cancer, Acta Oncologica, 56:3, 441-447, DOI: 10.1080 Background:The primary objective of this study was to compare the progression-free survival (PFS) at 12 weeks between patients treated with IGF-1R pathway modulator AXL1717 (AXL) and patients treated with docetaxel (DCT). Material and methods: The study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
(29 reference statements)
1
20
0
Order By: Relevance
“…The safety profile in this study concluded that there was a lower frequency of adverse events (AEs), especially neutropenia in the cohort of AXL1717 treatment. Unexpectedly, treatment-related fatal events were noted more commonly in this cohort (12 vs. 5) (72). On the whole, largely undesirable effects encountered in clinical settings emphasize the issue that identification of predictive markers indicative of responses to therapeutic strategies is timely and paramount to improving current therapy in carcinomas.…”
Section: Strategies To Overcome Emt-dependent Acquisition Of Egfr-tkimentioning
confidence: 77%
“…The safety profile in this study concluded that there was a lower frequency of adverse events (AEs), especially neutropenia in the cohort of AXL1717 treatment. Unexpectedly, treatment-related fatal events were noted more commonly in this cohort (12 vs. 5) (72). On the whole, largely undesirable effects encountered in clinical settings emphasize the issue that identification of predictive markers indicative of responses to therapeutic strategies is timely and paramount to improving current therapy in carcinomas.…”
Section: Strategies To Overcome Emt-dependent Acquisition Of Egfr-tkimentioning
confidence: 77%
“…Therefore, IGF1R seems to be a promising target in treating advanced NSCLC patients. Unfortunately, clinical trials failed to show benefit from targeting IGF1R in treating advanced NSCLC patients, partially due to the lack of biomarkers to select patient populations [ 59 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The practical feasibility of combination ALK/IGF-1R inhibition as a clinical strategy has been given a boost by recent research into the IGF-1R inhibitor AXL1717 in advanced non-small cell lung cancer. Early results have indicated that as a monotherapy AX1717 is as effective as existing chemotherapy and with less toxicity 22 24 . Moreover, the role of IGF-1R activation in non-small lung cancer prognosis has been very recently confirmed in a study of 326 NSCLC patients 25 .…”
Section: Discussionmentioning
confidence: 99%